Prickly pear for biogas production: technical‐economic validation of a biogas power installation in an area with a high prevalence of cacti in Italy. (4th March 2021) - Timpanaro, Giuseppe; Cosentino, Salvatore; Danzì, Carmelo; Foti, Vera T.; Testa, Giorgio
Abstract: The prickly pear in Italy is mostly used for human nutrition, although different cultivars of Cactaceae are intended for different uses around the world. Currently, there is a new bio‐economy for the prickly pear linked to the use of cladodes and fruit wastes for energy and numerous biotechnological derivatives. This paper focuses on the technical and economic validation of a bioenergy‐production installation, as the scientific literature has shown for years that it is possible to use the prickly pear in diets mixed with other materials. The varietal reconversion of part of the prickly pears produced domestically by traditional Italian farms geared exclusively to the production of fruit for human consumption is proposed. In this way, the introduction of biomass prickly pear varieties facilitates the construction of a shared biogas plant (organised as a district) and a network between the different actors in the area. The results show that, with the methanogenic potential of prickly pear, equal to 240 mc t −1, it is possible to feed a 300 kW plant, particularly favoured by the current system of Italian public incentives for investments in agro‐energy. This result can be achieved in a short supply chain, through the organization of a district composed of 30–40 producers, with an average size of 5 ha of prickly pears, in an area on the slopes of the Etna volcano where there is other biomass such as citrus pulp residues and olive pomace to be used in mixtures with cladodes. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd